SECOND LANGUAGE WRITING DEVELOPMENT IN CHILDHOOD: A CASE STUDY - Serrano, Raquel; Howard, Elizabeth R. (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Whereas most research on child second language acquisition has focused on the oral production of children, studies are needed to show their initial writing development in a second language. This paper aims to shed some light on this process, focusing on the English writing development of a native Spanish speaker enrolled in a two-way immersion program in the United States. Data for this presentation come from a longitudinal, national study which involves 484 students in 11 programs across the country. In this paper, we will present a case study of one of the students in the project, from the beginning of third grade until the end of fifth grade. The student’s writing samples will be discussed using an analytic rubric developed for the project. This rubric addresses three major aspects of writing –composition, grammar and mechanics– and provides a clear framework for investigating changes in writing ability over time.